A high-tap composite sodium iron phosphate positive electrode material, preparation method and application

By adopting a dual iron source strategy in the positive electrode materials of sodium ion battery, using cheap iron powder to replace expensive raw materials, and improving the tap density through ball milling and sintering processes, the problems of high cost and low tap density of sodium ion battery cathode materials are solved, and cost reduction and performance improvement are achieved.

CN119764443AInactive Publication Date: 2025-04-04PINGYU ZHONGXING ENERGY CO LTD

Patent Information

Application Number
CN202510273971.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery has high cost and low tap density, which limits the development of sodium ion batteries.

Method used

The double iron source strategy is adopted to partially replace the expensive iron phosphate or ferrous oxalate with inexpensive iron essence powder, and the tap density of the material is improved through ball milling and sintering processes.

Benefits of technology

It significantly reduces the cost of raw materials, increases the tap density of the positive electrode material, improves the energy density of the battery cell, and maintains the stability and electrochemical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764443A_ABST
    Figure CN119764443A_ABST
Patent Text Reader

Abstract

The present invention discloses a high-tap composite sodium iron phosphate positive electrode material, a preparation method and an application, wherein the preparation method comprises the following steps: S1, adding iron concentrate, other iron sources, phosphorus sources, sodium sources and carbon sources to deionized water and stirring to obtain a solid-liquid mixed slurry, wherein the other iron sources are ferrous oxalate or ferric phosphate; S2, ball milling / sand milling the solid-liquid mixed slurry to obtain a uniformly dispersed slurry, wherein the D50 particle size of the uniformly dispersed slurry is 0.3-0.6 μm; S3, drying, crushing and sieving the uniformly dispersed slurry in sequence to obtain a precursor powder; S4, sintering the precursor powder in an inert gas to obtain a high-tap composite sodium iron phosphate positive electrode material with a D50 particle size of 5-10 μm. The technical route developed by the present invention can significantly reduce the cost of raw materials (more than 10%), reduce processing energy consumption, and at the same time can increase the material tap density by more than 30%, while the material performance loss is less than 5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a high-tap composite sodium iron phosphate positive electrode material, a preparation method and an application thereof. Background Art

[0002] With the national dual carbon goals, the power storage market has ushered in space development opportunities. However, due to the scarcity of lithium resources and dependence on imports, existing lithium-ion batteries cannot meet the needs of the energy storage market. Among the many energy storage alternatives, sodium-ion batteries have the advantages of abundant raw materials, low cost, environmental friendliness, outstanding low-temperature performance, and high safety. They are considered to be the rising star of the next generation of energy storage batteries and are expected to completely replace lead-acid batteries in the future. They are widely used in energy storage, two-wheeled electric vehicles and even A00-class electric vehicle markets.

[0003] For sodium-ion batteries, the cost of cathode materials accounts for up to 40%, which is the key to restricting the development of sodium-ion batteries. Therefore, many researchers are attracted to focus on the research and development of sodium cathode materials. Among the large number of potential cathode materials, a type of composite sodium iron phosphate cathode material (hereinafter referred to as NFPP) has a general structural formula of Na 3+x Fe 2+x (PO4) 1+x (P2O7), 0≤x≤1, is characterized by the presence of both phosphate and pyrophosphate, and is moving from laboratory research and development to commercial production.

[0004] However, in most patents and public reports, NFPP is mainly produced by the iron phosphate process or the ferrous oxalate process. Although the NFPP prepared by these two processes shows excellent sodium storage performance, the cost of NFPP produced with iron phosphate and ferrous oxalate as the main raw materials is relatively high as they are fine chemicals. At the same time, iron phosphate and ferrous oxalate produce serious gas during the sintering process, resulting in a low tap density of the product (<1.1 g / cm 3 ), which is not conducive to improving the energy density of the battery cell. Summary of the invention

[0005] In order to overcome the defects of the prior art, the present invention provides a high-tap composite sodium iron phosphate positive electrode material, a preparation method and an application thereof, which can solve the technical problems of high cost and low tap density of the currently prepared sodium ion battery positive electrode materials.

[0006] The object of the present invention is achieved through the following technical solutions: In the first aspect, the present invention provides a high-tap composite sodium iron phosphate positive electrode material, the general structural formula of which is Na 3+ x Fe 2+ x(PO4) 1+x(P2O7), wherein 0≤x≤1; the high-tap composite sodium iron phosphate positive electrode material is prepared from iron concentrate, other iron sources, phosphorus sources, sodium sources and carbon sources, and the other iron sources are ferrous oxalate or ferric phosphate.

[0007] The present invention uses cheap iron concentrate (2,000 yuan / ton) to partially replace iron phosphate (about 11,000 yuan / ton) / ferrous oxalate (about 14,000 yuan / ton), which can achieve significant cost reduction. At the same time, it can also reduce the gas generation of iron phosphate and ferrous oxalate during the sintering process, and ultimately achieve the purpose of increasing the tap density of the product.

[0008] In one embodiment, the iron ore concentrate, other iron sources, phosphorus source and sodium source are mixed according to a molar ratio of Na:Fe:P of 4:(2.7-3.5):4, or a mass ratio of Na:Fe:P of 1:(1.64-2.12):1.35.

[0009] In one embodiment, the molar ratio of iron in the iron concentrate to other iron sources is 1:(2-29).

[0010] This raw material ratio can make the tap density of the prepared positive electrode material higher. When the mass of Fe exceeds this ratio, the stability of the overall composite structure will decrease. If the Fe content is lower than this ratio, the power storage capacity will decrease.

[0011] In one embodiment, the amount of the carbon source is 10%-20% of the output of the positive electrode material.

[0012] In one embodiment, the phosphorus source is at least one of phosphoric acid, sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, and sodium pyrophosphate.

[0013] In one embodiment, the sodium source is at least one of sodium carbonate, sodium nitrate, sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, and sodium pyrophosphate.

[0014] In one embodiment, the carbon source is at least one of starch, glucose, sucrose, citric acid, and ascorbic acid.

[0015] In a second aspect, the present invention provides an application of the above-mentioned high-tap composite sodium iron phosphate positive electrode material in the preparation of a sodium ion battery.

[0016] In a third aspect, the present invention also provides a method for preparing the above-mentioned high-tap composite sodium iron phosphate positive electrode material, comprising the following steps: S1, adding the ferrous oxalate, ferric phosphate, iron concentrate, phosphorus source, sodium source and carbon source into deionized water and stirring to obtain a solid-liquid mixed slurry; S2, ball milling / sand milling the solid-liquid mixed slurry to obtain a uniformly dispersed slurry, wherein the D 50The particle size is 0.3-0.6 μm; S3, drying, crushing and sieving the uniformly dispersed slurry in sequence to obtain a precursor powder; S4, sintering the precursor powder in an inert gas to obtain D 50 Highly tapped composite sodium iron phosphate positive electrode material with a particle size of 5~10 μm.

[0017] The method adopts a dual iron source strategy to synthesize the sodium ion battery positive electrode composite NFPP / C, which not only saves costs but also improves the tap density of the prepared composite positive electrode material. The method is easy to operate, can improve the preparation efficiency, does not require complex instruments and equipment, has high safety, and is easy to promote.

[0018] In one embodiment, in S3, the drying method includes air drying and spray drying, the air drying temperature is 70-100°C, and the air drying time is 2-10 h; the inlet air temperature of the spray drying is 150-250°C, the outlet air temperature of the spray drying is 60-120°C, and the feed rate of the spray drying is 0.5-30 mL / min.

[0019] In one embodiment, the inert gas is nitrogen, argon, an argon-hydrogen mixture or a nitrogen-hydrogen mixture.

[0020] In one embodiment, in S4, the sintering temperature is 300-550° C., the sintering time is 6-15 h, and the sintering heating rate is 1-10° C. / min.

[0021] This temperature range, time range and heating rate range can ensure the stability of the composite material structure and improve the tap density. Above this range will lead to structural instability, and below this range will result in a low tap density.

[0022] The main beneficial effects of the present invention are: The technical route provided by the present invention abandons the traditional ferric phosphate / ferrous oxalate technical route to produce composite sodium iron phosphate positive electrode materials, innovatively develops a dual iron source synthesis technology, and uses cheap iron concentrate to partially replace expensive ferric phosphate or ferrous oxalate, which can significantly reduce the cost of raw materials (≥10% or more). At the same time, the introduction of hard iron concentrate can also improve the ball milling / sand milling effect, shorten the sand milling time, and reduce processing energy consumption. More importantly, due to the high density of the iron concentrate itself, during the material sintering process, it can induce the newly formed composite sodium iron phosphate seeds to transform into a dense structure, and ultimately increase the tap density of the composite material by more than 30%, while the material performance loss rate is less than 5%. The composite sodium iron phosphate positive electrode material synthesized by the present invention has both cost and performance as the two major factors, and can comprehensively enhance the competitiveness of sodium iron pyrophosphate products. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be described in more detail below based on embodiments and with reference to the accompanying drawings, wherein: Figure 1 XRD patterns of NFPP / C composite cathode materials prepared in Examples 1-2 and 2-3; Figure 2 The scanning electron microscope images of Example 1-1, Example 1-3, Example 2-1, and Example 2-3, wherein Example 1-1 and Example 1-3 are irregular particles with a particle size distribution between 5 and 10 μm. Example 2-1 and Example 2-3 are spherical particles with a secondary spherical particle size distribution between 5 and 10 μm; Figure 3 The charge and discharge curves of the button-type half-cells prepared in Example 1-1 and Example 1-3 at a current of 0.1 C; Figure 4 The charge and discharge curves of the button-type half-cells prepared in Example 2-1 and Example 2-3 at a current of 0.1 C; Figure 5 The rate performance (0.1, 0.2, 0.5, 1, 2 and 5 C) of Examples 1-3 and 2-3 and the cycle performance at 1 C current. DETAILED DESCRIPTION

[0024] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0025] The present invention will be further described below in conjunction with the accompanying drawings.

[0026] Example 1-1 NFPP / C cathode material was prepared by ball milling-calcination process using iron ore concentrate, iron phosphate, sodium dihydrogen phosphate, sodium carbonate and anhydrous glucose as raw materials. Iron ore concentrate and iron phosphate were used as iron sources, iron phosphate and sodium dihydrogen phosphate were used as phosphorus sources, sodium dihydrogen phosphate and sodium carbonate were used as sodium sources, and anhydrous glucose was used as carbon source (1.56 g iron ore concentrate, 52.32 g iron phosphate dihydrate, 17.04 g anhydrous disodium hydrogen phosphate, 8.69 g sodium carbonate, 7.5 g anhydrous glucose). The specific operation steps are as follows: 1) Using iron concentrate, ferric phosphate, sodium dihydrogen phosphate, sodium carbonate and anhydrous glucose as raw materials, the ingredients are prepared according to the molar ratio of Na:Fe:P = 4:3:4, and the amount of anhydrous glucose used is 12% of the theoretical Na4Fe3(PO4)2(P2O7) output; 2) Add all the materials weighed in step 1) into the ball mill, add deionized water at a solid content of 40%, stir to mix the materials evenly, and then add zirconium balls with a diameter of 8 mm at a ball-to-material ratio of 5:1. Ball mill at 300 RPM for 6 h to obtain a slurry with a particle size of D 50 The precursor slurry is about 0.5 μm; 3) The slurry obtained by ball milling is transferred to an 80°C oven for drying to completely remove the moisture therein. After drying, the material is crushed by a high-speed grinder and sieved by a 300-mesh screen to collect finer precursor powder; 4) The precursor was loaded into a crucible and then sintered in a nitrogen atmosphere. First, it was pre-sintered at 350°C for 4 h at a heating rate of 5°C / min. Then, the temperature was raised to 520°C and calcined for 10 h at a heating rate of 3°C / min. After the material was cooled naturally, the NFPP / C composite cathode material was obtained.

[0027] Example 1-2 The raw material components are 3.12 g iron concentrate, 48.59 g ferric phosphate dihydrate, 19.89 g anhydrous disodium hydrogen phosphate, 6.57 g sodium carbonate, and 7.5 g anhydrous glucose. The remaining steps are the same as those of Example 1-1.

[0028] Examples 1-3 The raw material components are 4.68 g iron concentrate, 44.85 g ferric phosphate dihydrate, 22.74 g anhydrous disodium hydrogen phosphate, 4.45 g sodium carbonate, and 7.5 g anhydrous glucose. The remaining steps are the same as those of Example 1-1.

[0029] Example 2-1 NFPP / C cathode material was prepared by ball milling-calcination process using iron ore concentrate, ferrous oxalate, sodium dihydrogen phosphate, sodium carbonate and anhydrous glucose as raw materials. Iron ore concentrate and ferric phosphate were used as iron sources, ferric phosphate and sodium dihydrogen phosphate were used as phosphorus sources, sodium dihydrogen phosphate and sodium carbonate were used as sodium sources, and anhydrous glucose was used as carbon source (1.56 g iron ore concentrate, 40.69 g ferric phosphate dihydrate, 17.04 g anhydrous sodium dihydrogen phosphate, 8.69 g sodium carbonate, 7.5 g anhydrous glucose). The specific operation steps are as follows: 1) Using iron ore concentrate, oxalic acid, sodium dihydrogen phosphate, sodium carbonate and anhydrous glucose as raw materials, the ingredients are prepared according to Na:Fe:P=4:3:4, and the amount of anhydrous glucose is 10% of the theoretical Na4Fe3(PO4)2(P2O7) output; 2) Add all the materials weighed in step 1) into the sand mill, add deionized water at a solid content of 30%, stir to mix the materials evenly, and then add zirconium balls with a diameter of 2 mm at a ball-to-material ratio of 8:1. Ball mill at a speed of 2000 RPM for 3 h to obtain a slurry with a particle size of D50 The precursor slurry is about 0.5 μm; 3) The slurry obtained by sand grinding is screened to separate the slurry and zirconium beads. The separated slurry is spray dried at a spray drying temperature of 180°C; 4) The precursor was loaded into a crucible and then sintered in a nitrogen atmosphere. First, it was pre-sintered at 400°C for 3 h with a heating rate of 7°C / min. Then, the temperature was raised to 550°C and calcined for 11 h with a heating rate of 6°C / min. After the material was cooled naturally, the NFPP / C composite cathode material was obtained.

[0030] Example 2-2 The raw materials and contents are 3.12 g iron concentrate, 37.78 g ferric phosphate dihydrate, 17.04 g anhydrous sodium dihydrogen phosphate, 8.69 g sodium carbonate, and 7.5 g anhydrous glucose, and the remaining steps are the same as those in Example 2-1.

[0031] Example 2-3 The raw materials and contents are 4.68 g iron concentrate, 34.87 g ferrous oxalate dihydrate, 48.48 g anhydrous sodium dihydrogen phosphate, and 6.5 g anhydrous ferric phosphate. The remaining steps are the same as those in Example 2-1.

[0032] Comparative Example 1 Na4Fe3(PO4)2(P2O7) was prepared by conventional ferric phosphate technology. The specific preparation process was similar to that in Example 1, but no iron concentrate was added. Only ferric phosphate, sodium carbonate and anhydrous glucose were used as raw materials (56.06 g ferric phosphate dihydrate, 14.20 g anhydrous disodium hydrogen phosphate, 10.81 g sodium carbonate and 7.5 g anhydrous ferric phosphate). The rest of the process was exactly the same as that in Example 1-1.

[0033] Comparative Example 2 Na4Fe3(PO4)2(P2O7) was prepared by conventional ferrous oxalate process without adding iron concentrate. Only ferrous oxalate, sodium carbonate and anhydrous glucose were used as raw materials (43.59 g ferrous oxalate dihydrate, 48.48 g anhydrous sodium dihydrogen phosphate, 6.5 g anhydrous ferric phosphate). The rest of the process was exactly the same as Example 2-1.

[0034] Test Example 1 The positive electrode composite materials prepared in Example 1-1, Example 1-3, Example 2-1, and Example 2-3 were observed under a scanning electron microscope. The observation results are as follows: Figure 2 As shown in the figure, it can be seen that Example 1-1 and Example 1-3 are irregular particles with a particle size distribution between 5 and 10 μm. Example 2-1 and Example 2-3 are spherical particles with a secondary spherical particle size distribution between 5 and 10 μm.

[0035] Test Example 2 The positive electrode composite materials prepared in Examples 1-2 and 2-3 were subjected to X-ray diffraction tests, and the results were as follows: Figure 1 As shown. Figure 1 By comparison, it can be seen that the samples of Example 1-2 and Example 2-3 have no obvious impurities, indicating that the purity of Na4Fe3(PO4)2(P2O7) in different examples is relatively high.

[0036] Test Example 3 The positive electrode composite materials prepared in Example 1-1, Example 1-3, Example 2-1, and Example 2-3 were tested for specific capacity at a voltage of 2.0 to 4.0 V. The results are as follows: Figure 3 , Figure 4 As shown; the positive electrode composite materials in Examples 1-1~3, Examples 2-1~3 and Comparative Examples 1~2 were placed in button batteries and their electrochemical properties were tested. The results are shown in Table 1.

[0037] Table 1 Electrochemical properties of various cathode composite materials

[0038] contrast Figure 3 , Figure 4 As shown in Table 1, compared with the widely used iron phosphate (Comparative Example 1) and ferrous oxalate (Comparative Example 2) technology routes, the reversible capacity of Examples 1-1, 1-2, 2-1 and 2-2 shown in this patent is almost not lost. The first discharge capacity of Examples 1-3 and 2-3 at 0.1 C can also reach 101.5 and 103.2 mAh / g, and the reversible capacity loss is 4.7% and 2.8% respectively compared with their respective Comparative Examples 1 and 2.

[0039] According to the results in Table 1, the tap density of the material prepared by the technical route provided by the present invention is significantly improved. As shown in Table 1, the tap density of Comparative Example 1 prepared by the conventional iron phosphate technical route is only 1.105 g / cm 3 , while the tap densities of Example 1-1, Example 1-2, and Example 1-3 prepared by the technical route provided by this patent are 1.187, 1.328, and 1.633 g / cm respectively. 3 , with a maximum increase of 47.8%. Comparative Example 2 prepared by conventional ferrous oxalate technology has a tap density of only 1.035 g / cm 3 The tap densities of Example 1-1, Example 1-2, and Example 1-3 prepared by the technical route provided by the present invention are 1.157, 1.232, and 1.446 g / cm, respectively. 3, the highest increase is 39.7%. In addition, the technical route provided by the present invention also shows certain advantages in cost. According to the current price of iron concentrate of 2,000 yuan / ton, the price of ferrous phosphate dihydrate of 11,000 yuan / ton, ferrous oxalate dihydrate of 14,000 yuan / ton, disodium hydrogen phosphate anhydrous of 5,800 yuan / ton, sodium dihydrogen phosphate anhydrous of 6,800 yuan / ton, sodium carbonate of 5,200 yuan / ton, and anhydrous glucose of 4,000 yuan / ton, according to the formula provided in Examples 1-3, the BOM of producing 1 tNa4Fe3(PO4)2(P2O7) material is only 11,000 yuan / ton, compared with the conventional ferrous phosphate technical route (12,600 yuan / ton), the BOM cost is reduced by 12.7%; according to the formula provided in Examples 2-3, the BOM of producing 1 tNa4Fe3(PO4)2(P2O7) material is only 13,600 yuan / ton, compared with the conventional ferrous oxalate process (15,400 yuan / ton), the BOM cost is reduced by 11.7%. Obviously, the production of Na4Fe3(PO4)2(P2O7) by the technical route provided by the present invention has obvious advantages in material tap density and cost while ensuring material properties.

[0040] Test Example 4 The positive electrode composite materials prepared in Examples 1-3 and 2-3 were tested for rate performance at currents of 0.1, 0.2, 0.5, 1, 2 and 5 C, and for cycle performance at currents of 1 C. The results are shown in FIG. Figure 5 As shown, according to Figure 5 By comparison, after 50 cycles at 1 C current, the capacity retention rates of Examples 1-3 and 2-3 are 99.2% and 99.8%, respectively. At 1 C current, Examples 1-3 and 2-3 can also provide a reversible capacity of more than 95 mAh / g, and the 50-cycle retention rate is more than 99%, showing a good application foundation.

[0041] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "bottom", "top", "front", "back", "inside", "outside", "left", "right", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0042] Although the present invention is described herein with reference to specific embodiments, it should be understood that these embodiments are merely examples of the principles and applications of the present invention. It should therefore be understood that many modifications may be made to the exemplary embodiments and that other arrangements may be devised without departing from the spirit and scope of the present invention as defined by the appended claims. It should be understood that the various dependent claims and features described herein may be combined in a manner different from that described in the original claims. It should also be understood that features described in conjunction with individual embodiments may be used in other described embodiments.

Claims

1. A method for preparing a high-tap composite sodium iron phosphate positive electrode material, characterized in that: The steps include: S1, adding iron concentrate, other iron sources, phosphorus source, sodium source and carbon source into deionized water and stirring to obtain a solid-liquid mixed slurry, wherein the other iron source is ferrous oxalate or ferric phosphate; S2, ball milling / sand milling the solid-liquid mixed slurry to obtain a uniformly dispersed slurry, wherein the D 50 Particle size is 0.3~0.6 μm; S3, drying, crushing and sieving the uniformly dispersed slurry in sequence to obtain a precursor powder; S4, sintering the precursor powder in an inert gas to obtain D 50 Highly tapped composite sodium iron phosphate positive electrode material with a particle size of 5~10 μm.

2. The method for preparing a high-tap composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: In S3, the drying method includes air drying and spray drying, the air drying temperature is 70~100°C, and the air drying time is 2~10 h; the inlet air temperature of the spray drying is 150~250°C, the outlet air temperature of the spray drying is 60~120°C, and the feed rate of the spray drying is 0.5~30 mL / min.

3. The method for preparing a high-tap composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: The inert gas is nitrogen, argon, an argon-hydrogen mixture or a nitrogen-hydrogen mixture.

4. The method for preparing a high-tap composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: In S4, the sintering temperature is 300-550° C., the sintering time is 6-15 h, and the sintering heating rate is 1-10° C. / min.

5. A high-tap composite sodium iron phosphate positive electrode material, characterized in that: Its general structural formula is Na 3+x Fe 2+ x(PO4) 1+x (P2O7), wherein 0≤x≤1; prepared from iron concentrate, other iron sources, phosphorus sources, sodium sources and carbon sources, wherein the other iron sources are ferrous oxalate or ferric phosphate.

6. The high-tap composite sodium iron phosphate positive electrode material according to claim 5, characterized in that: The iron concentrate, other iron sources, phosphorus sources and sodium sources are prepared according to a molar ratio of Na:Fe:P of 4:(2.7-3.5):

4.

7. The high-tap composite sodium iron phosphate positive electrode material according to claim 6, characterized in that: The phosphorus source is at least one of phosphoric acid, sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, and sodium pyrophosphate.

8. The high-tap composite sodium iron phosphate positive electrode material according to claim 6, characterized in that: The sodium source is at least one of sodium carbonate, sodium nitrate, sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, and sodium pyrophosphate.

9. The high-tap composite sodium iron phosphate positive electrode material according to claim 6, characterized in that: The carbon source is at least one of starch, glucose, sucrose, citric acid and ascorbic acid.

10. Use of a positive electrode material obtained by the method for preparing a high-tap-compacted composite sodium iron phosphate positive electrode material according to any one of claims 1 to 4 or a high-tap-compacted composite sodium iron phosphate positive electrode material according to any one of claims 5 to 9 in preparing a sodium ion battery.

Citation Information

Patent Citations

  • All-iron-based sodium ion battery and preparation method thereof

    CN115064695A

  • High-valued recovery method of waste lithium iron phosphate / sodium iron phosphate battery positive electrode material

    CN115893345A

  • Preparation method and application of ferric sodium pyrophosphate positive electrode material

    CN117819512A

  • Iron-based sodium pyrophosphate / C composite material and preparation and application thereof in sodium ion battery

    CN118108202A

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method and application

    CN118472206A

Cited By

  • Pyrophosphate ferric sodium phosphate as well as preparation method and application thereof

    CN120039844A

  • Preparation method of composite ferric sodium pyrophosphate material

    CN120172384A